Pengembangan Game Edukasi Digital Tema Seni dan Bahasa dengan Metode Multimedia Development Life Cycle - Nurul, Hanan; Nugraheni, Dinar Mutiara Kusumo; Noranita, Beta; Bahtiar, Nurdin (Jurnal Sistem Informasi Bisnis, 2024)
Education for early childhood, especially for PAUD TK-B in the age range of 4-6 years, is crucial in providing and shaping the foundation of children's knowledge. An engaging teaching method will enhance children's interest in learning, thus the need for digital learning media as an alternative. One step in implementing digital learning is through Educational Games. This research is conducted by developing the PAUD TK-B Nurussunnah Educational Game using the Multimedia Development Life Cycle (MDLC) method. The game's validation includes usability aspects such as effectiveness, satisfaction levels, and adaptation to the TK-B curriculum. After development, the educational game undergoes alpha and beta testing using the black box method. Beta testing involves evaluating usability for the efficiency and satisfaction of TK-B students, with an effectiveness rate of 98.94%  and satisfaction rate of 88.57%. The interview results with expert teachers indicate that the educational game aligns with the curriculum at the educational unit level for PAUD. Thus, based on the research findings, the PAUD TK-B Educational Game application can be considered an alternative learning media for TK-B students.